2012
DOI: 10.1177/2165143412469400
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Transition Services for Deaf and Hard of Hearing Students

Abstract: This manuscript analyzed a survey of programs providing transition services to deaf and hard-of-hearing (D/HH) students. Quantitative analyses compared services offered by residential, large (35+ D/HH students), and small (<35 students) programs. Correlations across Employment Preparation, Post-school Preparation, and Transition Assessments were significant suggesting program consistency in offerings. ANOVA comparisons for Employment Preparation found that residential programs offered significantly more ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Some recent research in deaf education raises questions as to the adequacy of preparation for deaf individuals for employment after high school (Luft, 2012). Wagner, Newman, and Cameto (2004) indicated that the proportion of courses students who are deaf take that are related to career and technical education has dropped as emphasis on academic courses has increased, potentially leading to a decreased level of readiness for the workforce.…”
Section: Transition Planning Legislation Design and Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent research in deaf education raises questions as to the adequacy of preparation for deaf individuals for employment after high school (Luft, 2012). Wagner, Newman, and Cameto (2004) indicated that the proportion of courses students who are deaf take that are related to career and technical education has dropped as emphasis on academic courses has increased, potentially leading to a decreased level of readiness for the workforce.…”
Section: Transition Planning Legislation Design and Impactmentioning
confidence: 99%
“…Using the Transition Competence Battery to measure the transition strengths and needs of 53 deaf students in middle and high school, Luft and Huff (2011) found that the majority of students were lacking skills to acquire employment and to live independently. The authors suggested that school-based transition programming for students who are deaf should focus on long-term needs and skill building rather than focusing on skills needed immediately after high school (see also Luft, 2012).…”
Section: Transition Planning Legislation Design and Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…
For students who are deaf or hard-of-hearing (DHH), the transition process starting in high school and continuing in postsecondary environments is complex and involves factors from multiple levels of students ' contexts, including home, school, and community (Israelite, Ower, & Goldstein, 2002;McIlroy & Storbeck, 2011). Recent trends in postschool transition outcomes for students who are DHH are mixed (Luft, 2012). For example, overall postsecondary institution enrollment rates for DHH students are comparable with their peers (Newman et al, 2011).
…”
mentioning
confidence: 99%
“…The Individualized Education Program (IEP) is a formalized process that requires each student's transition team, including professionals, parents, and the student, to participate in articulating what goals and skills students are to work on in the coming year and progress toward postsecondary goals (Test, Fowler, White, Richter, & Walker, 2009). Transition planning for individuals who are DHH can be fraught with challenges, both logistically in providing full access for all members of the team (including the student and parents) and also in terms of identifying postschool opportunities that will allow the individual to realize his or her full potential (Luft, 2012). A potentially problematic area for students who are DHH in particular is that of interpreting; transition teams may not be familiar with working with an educational interpreter, or interpreters may not be qualified to provide high level of services needed for IEP team meetings (Schick, Williams, & Kupermintz, 2006).…”
mentioning
confidence: 99%